Irritant Dermatitis To Marking Nut Used As Hair Dye - Singh Shri Nath; Battamishra Asit Baran; Gardin Homyar Kobei; Shukla Kiran (Wolters Kluwer Medknow Publications, 2000)
x Marking nut is a known potent irritant. A part form its most common use by washerment as a black â€inkâ€ for marking clothes, it has been put to many indigenous uses in the villages of India. Here is a report of an ill-advised young girl who used its black juice as hair-dye and suffered from a sever irritant reaction. Use of marking nut, as a hair dye is probably unheard of.